Disaster Humor and Internet Memes During the Coronavirus Pandemic on the Example of Two Instagram Profiles - PREDOJEVIĆ, Željko (Anafora, 2023)
The article discusses the issue of the humorous discourse of Internet memes that emerged in response to the coronavirus (COVID-19) pandemic. Memes are studied within digital folklore as virtual surrogates of disaster jokes, the genre with which they have many similarities. They appeared immediately after the virus began spreading, thematizing the pandemic and new life situations caused by it, and are greatly influenced by media reports about the virus and its spreading. This article aims to analyze the humorous discourse of Internet memes, which is divided into four groups motivated by the way they approach the topic of the virus and the pandemic, and consequently they achieve a humorous effect compared to disaster jokes. The research is focused on internet memes posted on two Instagram profiles: eroGAG and Gospodar Pršljenova. The memes were posted at the beginning of the pandemic in Europe, in March and April 2020.